Chondroid syringoma: A case with unusual cytological findings - Kalyan Khan (Wolters Kluwer Medknow Publications, 2013)
Chondroid syringoma is a rare benign skin adnexal tumor, the cytological features of which have been published very rarely in the literature. A mucoid aspirate, abundant chondromyxoid matrix material, and epithelial components were suggested as diagnostic criteria. The reported case is one of chondroid syringoma confirmed by histopathology, the fine needle aspiration cytology of which yielded thin fluid-like material and microscopy revealed epithelial clusters with admixed smaller myoepithelial cells, background cyst macrophages, and only scanty chondromyxoid stromal elements. Including these cytological features of the present case among the diagnostic criteria for cytodiagnosis of chondroid syringomas might increase the chances of a definitive preoperative diagnosis and help in planning the extent of surgery.